Аналіз факторів внутрішнього та зовнішнього середовища регіону, що впливають на формування іміджевої політики регіону - Волобуєв, І.В. (Культура народов Причерноморья, 2013)
У статті проведено аналіз факторів внутрішнього та зовнішнього середовища регіону, що
впливають на якість іміджевої політики регіону. Охарактеризовано прояв впливу кожного з виділених
факторів для певних цільових груп та за конкретними напрямками регіональної іміджевої політики. Це
дозволятиме поєднувати необхідні складові іміджевої політики для окремих цільових груп таких як
населення регіону, представники бізнесу та туристи з метою формування привабливого економічного,
соціального, екологічного іміджу, іміджу інвестиційної привабливості та іміджу пріоритетного
напрямку регіону. В статье проведен анализ факторов внутренней и внешней среды региона, влияющих на
качество имиджевой политики региона. Охарактеризованы проявления влияния каждого из выделенных
факторов для определенных целевых групп и по конкретным направлениям региональной имиджевой
политики. Это позволит сочетать необходимые составляющие имиджевой политики для отдельных
целевых групп, таких как населения региона, представители бизнеса и туристы с целью формирования
привлекательного экономического, социального, экологического имиджа, имиджа инвестиционной
привлекательности и имиджа приоритетного направления региона. The article analyzes the factors internal and external environment of the region, affecting the quality
of image policy area. Manifestation of the influence of each the selected factors for specific target groups and in
specific areas of regional image policy has been characterized. Region is represented as a socio-economic,
structural and sectoral and spatial integrity, exposed internal and external factors that also form a unity in its
manifestation on the main target groups of image regional policy. Proved impossibility of a single separately
chosen direction of image policy for a specific target group, without regard to how it appears on the behavior of
other target groups. A region's population, businesses and tourists are the main target groups of image politics
of the region. Each of these groups at a certain level of influence exercised guided by their orientations to create
ideas about region. However, taking into account all the specific factors internal and external environment will
allow the necessary components combine to form the image policy (forming an attractive economic image, an
attractive social image, image investment attractiveness, an attractive environmental image, image priority
area) effective tool for specific target groups. Substantiated that the highest level of image quality policy can be
achieved only in a focused, coherent and comprehensive considering of the construction of the full range of the
most significant factors in their effect.